The Silent Threat of Human Metapneumovirus: Clinical Challenges and Diagnostic Insights from a Severe Pneumonia Case - Rubens Carmo Costa-Filho; Felipe Saddy; João Luiz Ferreira Costa; Leandro Reis Tavares; Hugo Caire Castro Faria Neto (Microorganisms)
Background: Human metapneumovirus (hMPV) is a respiratory pathogen that has gained increasing recognition due to advancements in molecular diagnostic tools, which have improved its detection and characterization. While severe disease manifestations are traditionally associated with pediatric, elderly, or immunocompromised patients, hMPV-related pneumonia in immunocompetent adults remains underexplored. Methods: This case report describes a 68-year-old male who developed severe community-acquired pneumonia (CAP) caused by hMPV despite being immunocompetent and having no significant comorbidities. The diagnosis was confirmed via multiplex RT-PCR, excluding bacterial and viral coinfections. Laboratory and imaging findings supported a viral etiology, while empirical antibiotics were initially prescribed due to diagnostic uncertainty. Results: The patient presented with respiratory symptoms that progressed to hypoxia, productive cough, and fatigue, requiring hospitalization. Imaging revealed bilateral ground-glass opacities and consolidations typical of viral pneumonia. Molecular diagnostics enabled accurate pathogen identification and guiding appropriate management, and the patient fully recovered with supportive care. Conclusion: This case underscores the importance of rapid molecular diagnostics for hMPV, reducing unnecessary antibiotics and enhancing management. Routine incorporation of hMPV testing into clinical protocols could improve the diagnosis and resource use. The development of vaccines, such as the IVX-A12 in phase II trials, offers hope for targeted prevention, underscoring the need for further research and therapeutic innovations.